ptk2 and mt2a Genes Expression in Gastritis and Gastric Cancer Patients with Helicobacter pylori Infection - Manouchehr Ahmadi Hedayati; Delniya Khani; Farshad Sheikhesmaeili; Bijan Nouri (Canadian Journal of Gastroenterology and Hepatology)
Background. ptk2 and mt2a genes contribute to the cell cycle during proliferation and apoptosis, respectively. Designing a case-control study including gastric adenocarcinoma and gastritis patients with and without Helicobacter pylori infection would lead to determinate of the correlations between ptk2 and mt2a genes expression with H. pylori infection in gastric antral epithelial cells. Methods. Overall, 50 and 30 gastric antral biopsy samples of gastric cancer (case group) and gastritis (control group) patients were included into study, respectively. All biopsy samples were collected considering the exclusion criteria including patients with a history of consumption of tobacco, alcohol, and anti-H. pylori drugs. Each patient group is divided into with and without H. pylori infection to detect cDNA fold changes of ptk2 and mt2a genes by using Real Time RT PCR. Furthermore, the presence of H. pylori virulence genes was detected directly by using specific primers and simple PCR on cDNA synthesized from total RNA of gastric antral biopsy samples. Results. A negative correlation was revealed between age and clinical manifestations with the ΔCt value of the ptk2 gene (P<0.05). The H. pylori iceA1/2 and cagE genes revealed positive and negative correlations with the ΔCt value of the ptk2 gene (P<0.05), respectively. Furthermore, a weak correlation was detectable between H. pylori babA2/B, oipA, and cagY genes and the ΔCt value of the mt2a gene in gastric antral epithelial cells of patients (P<0.1). Conclusions. The results of the current study opened a view for more investigation on the stunning roles of H. pylori infection in clinical outcomes through mt2a and ptk2 gene expression in gastric antral epithelial cells.